중족-족근 관절의 손상 - 김상림; 강현성; 신성진; Kim, Sang Rim; Kang, Hyun Sung; Shin, Sung Jin (대한족부족관절학회지, 2012)
Lisfranc joint injuries are rare and account for 0.2% of all injuries. The pattern of Lisfranc injuries varies from low-energy ligamentous sprain to high-energy fractures or crushing injuries. Early diagnosis and appropriate treatment of Lisfranc injuries are important to prevent chronic foot pain and dysfunction.